Penting Struktur Data Tree dalam Mengelolah Data Komputer - Intan Sahyuni; Aura Chintiya Bella; Muhammad Rijal; Syaira Ramadhani; Eksyel Bongga Upa'; Suci Dian Azzahra; Ketrin Rinayanti Manullang (INDO PUBLISHING, 2026)
The rapid development of information technology has increased the need for efficient and structured data management. Large amounts of data require systems that can organize, process, and access information quickly and accurately. One of the most widely used solutions in computer science is the tree data structure. This structure organizes data hierarchically, making searching, inserting, and deleting processes more efficient. This study aims to analyze the importance of tree data structures in managing computer data and compare their performance with other data structures such as arrays and linked lists. The research method used is a quantitative approach with descriptive-experimental methods through simulations of several data structures using different data sizes. The results show that binary search trees provide faster search performance compared to linear data structures, especially for large datasets. In addition, tree structures are highly effective for managing hierarchical data such as file systems and databases. Therefore, tree data structures are considered an important component in improving the efficiency of modern computer data management.